Embodied Cognition in Dance and Choreography (2015)
Humans are generally equipped with a capacity for cognitive function at birth, meaning that each person is capable of learning or remembering a certain amount of information. This paper, therefore, joins in the growing discussion on the mental process involved in the creation, learning and execution of dance movements. This process is referred to as the cognitive process which borders on the basic phenomena of cognition: perception, attention, memory and imagination. This interdisciplinary research establishes the place of psychology in dance scholarship